Symbolic dimensions of the biblical Sarah: from Judaism to Christianity (Circe de clásicos y modernos, 2022)
The article reviews the successive symbolic dimensions that the figure of Sarah, Abraham’s wife, acquires, from its biblical origins in Genesis of LXX to the comments of the Fathers of the Church, focusing especially in the interpretations of Philo of Alexandria and Paul of Tarsus. Sarah symbolizes in Philo virtue–ἀρετή– and wisdom –σοφία– and, by means of a particular exegesis of Gn 18. 11, virginity in its pure state. Paul’s version (Gal 4. 21-31) of the story of Sarahand Hagar displaces the Jews from the inheritance of the promise and places Christians on that pedestal, and Sarah as the mother of Christianity.
Keywords: Sarah; Hagar; Abraham; Philo of Alexandria; Paul of Tarsus